Nutrition competencies for medicine: an integrative review and critical synthesis. Issue 3 (25th March 2021) - Lepre, Breanna; Mansfield, Kylie J; Ray, Sumantra; Beck, Eleanor J
Abstract : Objective: Globally, 11 million deaths are attributable to suboptimal diet annually, and nutrition care has been shown to improve health outcomes. While medically trained clinicians are well-placed to provide nutrition care, medical education remains insufficient to support clinicians to deliver nutrition advice as part of routine clinical practice. Competency standards provide a framework for workforce development and a vehicle for aligning health priorities with the values of a profession. Although, there remains an urgent need to establish consensus on nutrition competencies for medicine. The aim of this review is to provide a critical synthesis of published nutrition competencies for medicine internationally. Design: Integrative review. Data sources: CINAHL, Medline, Embase, Scopus, Web of Science and Global Health were searched through April 2020. Eligibility criteria: We included published Nutrition Competency Frameworks. This search was complemented by handsearching reference lists of literature deemed relevant. Data extraction and synthesis: Data were extracted into summary tables and this matrix was then used to identify common themes and to compare and analyse the literature. Miller's pyramid, the Knowledge to Action Cycle and the Dreyfus model of skill acquisition were also used to consider the results of this review. Results: Using a predetermined search strategy, 11 articles were identified. Five common themes were identified and include (1) clinical practice, (2) health promotion and disease prevention, (3) communication, (4) working as a team and (5) professional practice. This review also identified 25 nutrition competencies for medicine, the majority of which were knowledge-based. Conclusions: This review recommends vertical integration of nutrition competencies into existing medical education based on key, cross-cutting themes and increased opportunities to engage in relevant, skill-based nutrition training.